2011
DOI: 10.1159/000324933
|View full text |Cite
|
Sign up to set email alerts
|

Public Perspectives on Returning Genetics and Genomics Research Results

Abstract: Background: The debate about returning research results has revealed different perspectives among researchers, participants and advisory groups with participants generally interested in obtaining their results. Given this preference, policies regarding return of individual research results may affect whether a potential subject chooses to participate in a study. Public attitudes, particularly those of African-Americans, toward this issue have been understudied. Methods: In 2008–2009, we convened 10 focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
65
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 95 publications
12
65
0
Order By: Relevance
“…One possible explanation for this difference though is that it was "created" by the research design: the three hypothetical scenarios were presented in the same order to all participants (no mention of results first, specified that results would not be returned second, and specified that results would be returned third), and to be truly convincing the order would need to be randomly varied between participants to ensure that the results are not the outcome of an "order effect." On the other hand, our findings are consistent with two recent surveys utilizing hypothetical scenarios in other populations which have similarly shown that people are more willing to participate in genomics studies when individual test results have been offered than when results have not been offered, providing some support for the assertion that our findings are not a mere artifact of the study design (O'Daniel and Haga 2011;Kaufman et al 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…One possible explanation for this difference though is that it was "created" by the research design: the three hypothetical scenarios were presented in the same order to all participants (no mention of results first, specified that results would not be returned second, and specified that results would be returned third), and to be truly convincing the order would need to be randomly varied between participants to ensure that the results are not the outcome of an "order effect." On the other hand, our findings are consistent with two recent surveys utilizing hypothetical scenarios in other populations which have similarly shown that people are more willing to participate in genomics studies when individual test results have been offered than when results have not been offered, providing some support for the assertion that our findings are not a mere artifact of the study design (O'Daniel and Haga 2011;Kaufman et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…A handful of studies addressing interest in receiving personal results specifically from genomics research in diverse populations using a focus group methodological approach have recently been conducted (Bollinger et al 2012;O'Daniel and Haga 2011). One of these studies suggested that individuals from diverse backgrounds seem interested in receiving personal results from genomics research (Bollinger et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising [O'Daniel and Haga 2011] and, as our results suggest, partly reflects well-known lower levels of trust in biomedical research and access to clinical care in some AA communities [Corbie-Smith et al, 2002;LaVeist et al, 2000]. However, our results also identified several additional factors that may contribute to lower levels of interest.…”
Section: Discussionsupporting
confidence: 75%
“…[7][8][9] Adult participants in research strongly voice an interest in being offered genetic research results, including those incidental to the primary aims. 10,11 The empirical evidence to understand parental attitudes toward the sharing of genomic research results derived from research with children has just begun to be explored. [12][13][14][15] There is also considerable debate about the extent to which family members should be informed of potentially relevant genomic information gathered in a pediatric context.…”
mentioning
confidence: 99%